Energy–structure coupling mechanism and damage evolution model of red sandstone during soaking–softening process - Jingjing Zhang; Ning Liang (PLoS ONE, 2026)
To reveal how different soaking times affect red sandstone’s softening characteristics, this study analyzed red sandstone’s mineral composition, meso-structure, mechanical properties, and energy evolution laws. A damage constitutive model was established based on mechanical property testing and microstructure determination experiments of rock samples. It considers the initial compaction nonlinear section. The prediction bias in the energy dissipation theory damage model during the compaction stage was corrected based on the correction coefficient. The deterioration of mechanical properties of rock samples is positively correlated with immersion time. The results showed that water soaking caused feldspar, calcite, and other minerals to dissolve. It also reduced clay minerals and made pore development more intense. The mechanical properties of rock samples gradually decrease. This happened as soaking duration increased. When the soaking time reached 150 days, the cumulative deterioration degrees reached 44.25% and 30.78% respectively. The turning point of dissipated energy moved forward. The growth inflection point of the damage variable also advanced. The rock sample damage model fitted well with the experimental curve. It could accurately characterize the softening process. The research results explained the “time–structure–energy–damage” coupling mechanism. This mechanism applies to red sandstone softening under water–rock interactions. The explanation covered both macro and meso perspectives. It provided key theoretical support for red sandstone engineering stability assessment and long-term service safety.